A formação da democracia moderna: a contribuição das ideias religiosas dos puritanos no século XVII. - Correia, Fábio José Barbosa (2022)
From the 20th century onwards, the main declared anti-democratic regimes succumbed. Communism, Fascism and Nazism were considered utterly deplorable, on account of the atrocities they committed; duly documented by history. A democratic wave then swept over the Western world; mainly. By all indications, the choice for democracy was ratified. It is true that democracy itself is not a perfect regime. However, no better alternative has been presented. So, the option has been to make the necessary adjustments in the democratic environment itself. Despite this, it is estimated that at least half of the world's population has never experienced it and lives under regimes that vary between fanatical nationalism and religious fundamentalism, in addition to balances of totalitarianism. Democracy is not a naturally given regime. As a rule, it needs to be conquered from the desire for freedom. Although the establishment of its origin is not a consensus, it is generally accepted that its first version appeared in ancient Greece, around the fifth century BC. Its basic aspect lies in the fact that sovereignty must emanate from the people and must be directly exercised by them. All must rule all. With the demographic explosion and the consequent growth of cities, this first version became unviable, since the activity of governing requires almost exclusive dedication and with the emergence of the Modern State, new demands would require the commitment of the people in other areas. From then on, gradually, the idea of democracy was abandoned, with a new cycle of monarchies, absolutisms and despotisms being resumed; until, finally, it disappeared completely. With the advent of Christianity, a kind of parallel reality emerges: the people again exercise sovereignty, electing the leaders of their churches. Representative democracy was then being conceived in the minds of Christians. The transition to a secular regime of government occurs, initially, in England in the 17th century, with the involvement of the Puritans in politics; alternative found to try to definitively implement the Reformation in the English church, since it was state-owned. The reaction of the Stuart dynasty, which sought to promote a return to Roman Catholicism, was strong and immediate. Then, a great civil war begins: on the one hand the Puritan Parliament and the New Model Army, its powerful army of the “round heads”, under the command of the Puritan Oliver Cromwell and on the other the King; who had been defeated and beheaded. Here, democracy reappears. The common thread of history has preserved sovereignty, which emanates from the people; now exercised through elected representatives. Some must rule all; the great novelty of the new regime. Then, effectively, representative democracy, also called modern democracy, emerges. This is what we will try to demonstrate in four chapters: in the first, we will present a panoramic view of Puritanism. In the second chapter, we will present the theological and doctrinal bases of the ecclesiastical representative government of the Puritans. In the third and most important, we will demonstrate that representative democracy arises from the political involvement of the Puritans and in the fourth and last, we will present some indirect consequences of this involvement of the Puritans with politics.